Exploring the causal relationship between plasma proteins and postherpetic neuralgia: a Mendelian randomization study - Wei, Qiuyu; Yu, Shaoyong; Luo, Yi; Song, Xinghui; Qin, Pin; Li, Rongji; Sun, Weichao; Wang, Jin; Wu, Gang (Frontiers in Neurology, 2025)
BackgroundThe proteome represents a critical reservoir of potential therapeutic targets for neurological diseases. This study aims to investigate the causal relationship between plasma proteins and postherpetic neuralgia.MethodsWe performed a two-sample Mendelian Randomization (MR) analysis utilizing genome-wide association study (GWAS) summary statistics from the Decode Genetics dataset (4,907 plasma proteins) and the FinnGen database (490 PHN cases and 435,371 controls). Instrumental variables (IVs) were carefully selected based on stringent criteria to ensure their relevance, independence, and exclusivity. Multiple MR methods, including inverse variance weighting (IVW), MR-Egger, Simple mode, Weighted mode and weighted median, were employed to assess causal relationships. Sensitivity analyses, including leave-one-out analysis, were conducted to confirm the robustness of the findings.ResultsOur analysis identified 14 plasma proteins with significant causal associations with PHN, all p < 0.05. Elevated levels of four proteins (NCF1, ATRN, PIANP, and CD48) were associated with an increased risk of PHN, while higher levels of 10 proteins (GABARAPL2, MAP1LC3B, ARF3, KIR2DL5A, DLK1, COLEC12, GPI, SEMG2, EIF4B,and HFE2) were linked to a decreased risk. These findings were supported by sensitivity analyses, which confirmed the robustness of the results and ruled out genetic pleiotropy as a potential bias.ConclusionThis MR study provides strong evidence for the causal role of specific plasma proteins in the development of PHN. These proteins could serve as potential biomarkers and therapeutic targets for PHN. Future research, including randomized controlled trials, is essential to validate these findings and further explore their clinical applicability.